Articulação entre o professor do Atendimento Educacional Especializado (AEE) e o professor do ensino comum: Um estudo das perspectivas do trabalho colaborativo em duas escolas municipais de Fortaleza - Araruna, Maria Rejane (2018)
This thesis aims to analyze the conditions for the construction of a collaborative work between the teacher of the Specialized Educational Assistance (AEE) and the common teaching teacher, in two municipal schools of Fortaleza, from the development of an intervention research. The nacional and international scientific literature (BRAUN, MENDES, 2006; KAMPWIRTH, 2003; MURAWSKI, SWANSON, 2001) that deals with experiences in inclusive practices indicates the collaborative work among teachers as a positive strategy in solving problems related to the teaching- learning. The bibliographic review and the foundations of the study contemplate researches on the collaborative work, the formation and the teaching knowledge and the presuppositions implied in the transformation of the pedagogical practices articulated to the theory of the change. The methodology was the intervention research characterized by the production of collective and innovative pedagogical practices and the sharing of knowledge in which the participants promote actions with the intention of change. Two ESA teachers and eight teachers participated in the study. The study consisted of four stages: i. exploratory / initial; ii. training and work meetings for the planning of collaborative strategies; iii. implementation of strategies for collaboration among teachers; iv. final evaluation. The results indicate that the articulation between the two groups of teachers (ESA teachers and teachers of the common room) occurs in an unsystematic way, without prior planning or defined intentions, as a rule with a view to attending the emergence of everyday situations with students of Special Education. It was evidenced that, although the teachers expressed their willingness to articulate, some factors limit the initiatives in this sense. Working conditions are incompatible with an innovative approach to teaching, work overload to teachers, structural conditions and overcrowding in the environments in which they work, are some of the aspects that greatly disfavour the articulation and implementation of practices collaborative. The study highlights the need to restructure teachers' schedules so that they can hold meetings for study and collaboration between them. It is necessary to invest in continuing education systems that mobilize collaborative practices and not just assemblages and fortuitous articulations that strengthen the theory-practice relationship so that they focus the demands on these students. Under these circumstances, for collaborative work between teachers to succeed, it must be understood as a process under construction and not as an episode to solve emergency problems in the inclusive context. The conditions for the development of collaborative work among teachers have great potential in schools, their main challenges are also their great potential factors. Therefore, it is linked to the overcoming of limiting organizational factors evidenced by the study, mainly from an institutional reorganization. These are important indicators and an essential condition for the implementation of innovative and collaborative practices among the groups of teachers surveyed. It is also important to highlight the relevance of the collaborative work between these two groups of professionals in the school, as it can contribute to the mobilization and professional development of teachers and the improvement of student learning outcomes and their inclusion process.